Yenidoğan Yoğunbakım Ünitelerinde Sağlık Hizmeti İlişkili Kan Akım Enfeksiyonlarının Prevalansı; İlk Ulusal Nokta Prevalans Çalışmasının Sonuçları - (:unkn) unknown (My University, 2015)
Amaç: Yenidoğan yoğun bakım ünitelerinde (YYBÜ) yatan hastalar sağlık hizmeti ilişki (SHİE) enfeksiyomlar için yüksek risk altındadır. Biz ulusal çok merkezli bu çalışmada sağlık hizmeti ilişkili kan akım enfeksiyonun (SHİKAE) prevalansını ve eşlik eden risk faktörlerini değerlendirdik. Materyal ve Metod: Biz 38 YYBÜ'de SHİKAE için nokta prevalans çalışması yaptık. Anket tarihinde yatmakta olan hastalar çalışmaya dahil edildi. Bulgular: SHİKAE'lerin %61.9'u (n=88) klinik sepsis, %35.2'si (n=50) laboratuar konfirme kan akım enfeksiyonu ve %2.9'u (n=4) kateter ile ilişkili kan akım enfeksiyonuydu. SHİKAE olan hastaların %38'inde (n=54) etken mikroorganizmalar tespit edildi. En sık tespit edilen etken patojenler; kogagülaz negative stafilokok (n=34, 25.7%), Candida spp. (n=10, 7%) idi. Total parenteral nutrisyon, nazogastrik sonda, santral venöz kateter, High Efficiency Particulate Air (HEPA) yokluğu, gastrointestinal sistem hastalığı, kateter ile ilişkili enfeksiyonları önlemek için bundle uygulamasının yapılmaması, her bir küvez başında el dezenfektanının olmaması, yatış süresinin üç günden fazla olması ve hasta yaşının 30 günden fazla olması SHİKAE için risk faktörü olarak tespit edildi. Dört haftalık izlem sonucunda 33 hasta (%3.5) öldü, bu hastaların 13'ü (%39.3) SHİE nedeniyle öldüü tespit edildi. SHİKAE ölüm için risk faktörü olarak tespit edilmedi. Sonuç: Çok merkezli bu çalışma göstermiştir ki YYBÜ kaynaklı enfeksiyonların prevalansı yüksektir. Bu enfeksiyonların önlenmesi ulusal öncelik olmalıdır.

Purpose: Patients admitted to neonatal intensive care units (NICUs) are at high risk of Healthcare-Associated Bloodstream Infection (HABSI). We conducted a national multicenter assessment of HABSI in NICUs to determine the prevalence of infections and describe associated risk factors. Material and Methods: We conducted a point prevalence survey of HABSI in 38 NICUs. Patients present on the survey date were included. Data on demographics, underlying diagnoses, therapeutic interventions/treatments, infections, and outcomes were collected for all NICU patients. Results: A total of 933 patients in 38 NICUs participated in the study, 142 of whom had HABSI, corresponding to a prevalence of 15.2%. The reported HABSI were clinical sepsis (n=88, 61.9%), laboratory-confirmed bloodstream infection (n=50, 35.2%) and catheter related infection (n = 4, 2.9%). Causative microorganisms were isolated in 54 (38%) patients with HABSI. The most common causative pathogens were coagulase negative Staphylococcus (n=34, 25.7%) and Candida spp. (n=10, 7%). The risk factors for HABSI were total parenteral nutrition, nasogastric feeding tube, central venous catheter, absence of High Efficiency Particulate Air (HEPA), gastrointestinal system disease, carrying out the preventive application bundle for catheter related infections, absence of next to each incubator disinfectant, duration of hospitalization more than 3 days and post-natal age more than 30 days. At 4-week follow up, 33 (3.5%) patients had died, 13 (39.3%) of whom died from healthcare-associated infections. HABSI were not found to be risk factors for death (p>0.05). Conclusion: This national multicenter study documented the high prevalence of NICU-acquired infections. Preventing these infections should be national priority.
Prevalence of Newborn Intensive Care Unit-Acquired, Healthcare-Associated Blood-Stream Infections in Neonatal Intensive Care Unit Patients: Results From The First National Point-Prevalence Survey
Keywords: Temel Sağlık Hizmetleri